Molecular microbiological characteristics of gingival pockets in the periodontal diseases of dogs - Polkowska Izabela; Tymczyna-Borowicz Barbara; Gołyńska Magdalena; Nowicka Beata (Journal of Veterinary Research, 2023)
Canine periodontitis results among other factors from a disturbed balance of dental plaque microflora and an inadequate host inflammatory response to a stimulus. This investigation sought to identify microorganisms associated with canine periodontitis.